Pengaruh Desain Lobby Universitas Matana Terhadap Kenyamanan Termal, Visual, Akustik, dan Kesehatan - Muhammar Khamdevi; Gabriella Kurniawan; Theophilus Wahyudi; Leonardo Marcellino; Andre Pratama (Prodi Arsitektur Universitas Matana, 2020)
The Matana University Lobby was inaugurated in 2019. This lobby aside from being a transitional space from the entrance to other room functions, it also accommodates the activities of every student and other user, which is also equipped to support activities for visitors who want to get information and complete administrative issues. Therefore Lobby must be able to provide comforts for its users, in this case thermal, visual, acoustic, and health. How is the effect of Matana University Lobby design on building comforts: thermal, visual, and acoustic. This study measures user responses, in this case students, regarding Lobby design and its effect on the comforts of the building. The research method used is a quantitative method which is done partially for each dependent variable. The results showed in general the positive effect of Matana University Lobby design on building comforts.